Calculation and Analysis of the Meshing Efficiency of Spur Gear - Yang Shiping; Fan Hui; Zhu Guanghui (Jixie chuandong)
The meshing efficiency calculation method of spur gear is studied,from the power consumption launched,the meshing efficiency calculation function of straight tooth cylindrical gear is deduced,the variation average friction coefficient instead of assuming constant friction factor is introduced,the more accurate meshing efficiency calculation formula of involute gear is obtained.Combined with the Matlab software simulation analysis,the relationship between the gear meshing efficiency and the gear basic parameters is obtained,which can provide some methods to improve the efficiency of gear transmission.